(untitled) (Colombia Medica, 2023)
This letter focuses on the interesting article entitled “Melancholy as a Healthy Strategy in Times of Great Human Crisis” 1 , where a series of very respectful observations and reflections are made: First, we raise the convenience of reorienting the worldview presented in the article since it establishes a tragic image of life (death). Not only because it implies the idea of the end of the world as the basis of the population’s anxieties and obsessions but also because it presupposes that the modernly conceived world is unlivable due to the level of stress endured because of uncertainty and change. Moreover, it presents melancholy and bitterness as strategies to be applied as a remedy to the living crisis and to achieve mental health. Certainly, behaviors that do not have a profile of harmony or internal coherence in the subject but of disorganization and a healthy lack of response to life. The second observation is a theoretical proposal of a materialistic and systemic, i.e., scientific nature. While it is true that the conditions we live in today are complex, uncertain and changing. It is also true that theoretical proposals such as resilience come from social psychology, which proposes assertive, proactive behaviors that look more positively to the health of citizens without reaching romantic explanations such as the possible exercise of freedom (subjectivism and idealism) or the ideal of the self (patent presence of psychoanalysis). These terms are not only insubstantial but have no known therapeutic correlation. Therefore, the population demands a clear and realistic vision of mental health to structure concrete ways out of their stress, depression, or anxiety.